Is there a correlation between right bronchus length and diameter with age? - Otoch, José Pinhata; Minamoto, Hélio; Perini, Marcos; Carneiro, Fred Olavo; Artifon, Everson Luiz de Almeida (Journal of Thoracic Disease, 2013)
Objective: Right main bronchial anatomy knowledge is essential to guide endoscopic stent placement in modern era. The aim is to describe right bronchial anatomy, cross-area and its relation with the right pulmonary artery and patient's age. Methods: One hundred thirty four cadaveric specimens were studied after approval by the Research and Ethics Committee at the University of São Paulo Medical School and Medical Forensic Institute of São Paulo. All necropsies were performed in natura after 24 hours of death and patients with previous pulmonary disease were excluded. Landmarks to start measurement were the first tracheal ring, vertex of carina, first right bronchial ring, and right pulmonary artery area over the right main bronchus. After mobilization, the specimens were measured using a caliper and measurement of distances was recorded in centimeters at landmarks points. All the measures (distances, cross sectional area and planes) were performed by three independent observers and recorded as mean, standard error and ranges. Student t test was used to compare means and linear regression was applied to correlate the measurements. Results: From 134 specimens studied, 34 were excluded (10 with previous history of pulmonary diseases, surgery or deformities and 24 of female gender). Linear regression showed proportionality between tracheal length and right bronchus length; with the area at first tracheal ring and carina and also between the cross sectional area at these points. Linear regression analysis between tracheal length and age (R=0.593 P